Nerve Growth Factor Regulation by TNF-α and IL-1β in Synovial Macrophages and Fibroblasts in Osteoarthritic Mice - Shotaro Takano; Kentaro Uchida; Masayuki Miyagi; Gen Inoue; Hisako Fujimaki; Jun Aikawa; Dai Iwase; Atsushi Minatani; Kazuya Iwabuchi; Masashi Takaso (Journal of Immunology Research)
To investigate the role of macrophages as a regulator and producer of nerve growth factor (NGF) in the synovial tissue (ST) of osteoarthritis (OA) joints, the gene expression profiles of several inflammatory cytokines in the ST, including synovial macrophages and fibroblasts, of OA mice (STR/Ort) were characterized. Specifically, real-time polymerase chain reaction analysis was used to evaluate the expression of tumor necrosis factor- (TNF-) α, interleukin- (IL-) 1β, IL-6, and NGF in CD11b+ and CD11b– cells isolated from the ST of a murine OA model. The effects of TNF-α, IL-1β, and IL-6 on the expression of NGF in cultured synovial cells were also examined. The expression of TNF-α, IL-1β, IL-6, and NGF in the ST of STR/Ort was higher than that in C57/BL6J mice. Compared to the CD11b– cell fraction, higher expression levels of TNF-α, IL-1β, and IL-6 were detected in the CD11b+ cell fraction, whereas no differences in the expression of NGF were detected between the two cell fractions. Notably, TNF-α upregulated NGF expression in synovial fibroblasts and macrophages and IL-1β upregulated NGF expression in synovial fibroblasts. IL-1β and TNF-α may regulate NGF signaling in OA joints and be suitable therapeutic targets for treating OA pain.